Effectiveness of caregiver-provided individual cognitive interventions among older adults with major neurocognitive disorder: a systematic review - Bobrowicz-Campos, E.; Silva, R.; Santos-Costa, P.; Almeida, M. L. (Atas do VI Congresso de Investigação em Enfermagem Ibero-Americana e de Países de Língua Oficial Portuguesa, 2021)
Introduction: The increase in the older population led to a higher prevalence of major neurocognitive disorder (mNCD). mNCD is a clinical syndrome caused by neurodegenerative processes and characterized by changes in several cognitive domains. Nonpharmacological interventions have emerged as an alternative to therapeutic approaches used to manage this clinical condition. Home-provided programs of individual cognitive intervention (CI), developed by caregivers in a one-to-one interaction, constitute a potentially suitable option. However, their successful implementation requires the synthesis of the effectiveness-related evidence. Objectives: The objective of this review was to synthesize the best available evidence on the effectiveness of individual CI provided by caregivers for improving (i) general cognitive functioning and functioning in specific cognitive domains (such as memory, attention, verbal fluency, and problem-solving); (ii) behavior, mood, and daily living activities; (iii) as well as social functioning and quality of life in community-dwelling older adults, aged 60 years and over, with mNCD. Methodolog y: A comprehensive search strategy aimed at relevant published and unpublished experimental studies, from January 1995 to March 2018, that examined the effectiveness of individual CI provided to older adults with mNCD by their caregivers. For comparison purpose, usual care, or alternative therapeutic intervention were considered. The methodological quality was assessed by two independent reviewers, using the Joanna Briggs Institute (JBI) Critical Appraisal Checklists. For data extraction the standardized tool from the JBI System for the Unified Management, Assessment and Review of Information was used (Silva, Cardoso, Abrunheiro, Almeida, & Apóstolo, 2016). Results: The search identified 2257 studies. The screening and eligibility assessment procedures resulted in the inclusion of eight randomized controlled trials and two quasi-experimental studies. The total sample was 844 dyads (older adults and caregivers). Regarding intervention of interest, it was provided in the form of stimulation, or rehabilitation, or reality orientation programs. In four cases its implementation was supported exclusively by the caregivers, and in six cases the additional support of health professionals or the research team was reported. The caregiver-provided individual CI was shown to improve general cognitive functioning, and functioning in domains of memory, attention, verbal fluency and problem-solving. The additional benefits for stabilization of neuropsychiatric symptoms and increase in autonomy, in daily living activities were also found. However, the level of evidence presented for these last two outcomes was quite low. Regarding quality of life, none of the reviewed studies reported significant changes. Finally, none of the included studies provided data on social functioning (Silva et al., 2020). Conclusions: The caregiver-provided CI was shown to be associated with improved cognitive performance and stabilization of neuropsychiatric symptoms. It also revealed certain (although reduced) benefits in daily living activities. However, its impact on quality of life was found to be not significant. The review findings support the utility of the caregiver-implemented CI in a community setting. However, further research on the impact of sociodemographic and clinical factors on the intervention effects is needed, as these factors seem to interfere with the successful implementation of the intervention. To reinforce current evidence, the methodological quality of future studies should be improved.